Differences and Similarities in Motives to Decrease Drinking, and to Drink in General Between Former and Current Heavy Drinkers—Implications for Changing Own Drinking Behaviour - Rowicka, Magdalena (Frontiers in Psychology, 2022)
The evidence on why people initiate or cease drinking is vast; however, little is known regarding why people change their frequency and amount of drinking from intense (heavy or dependent drinking) to recreational (with little risk). Therefore, the purpose of this study was to investigate how drinking motives and motives to decrease drinking differ between former heavy drinkers (problematic and dependent), current dependent, and current recreational drinkers. Data were obtained from four groups of individuals (n = 263) using alcohol with different severity. The participants were Polish young adults aged between 18 and 35 years. About 53% of the sample were women. The Alcohol Use Disorder Identification Test (AUDIT) was used to assess the level of drinking; the Drinking Motive Questionnaire-Revised Short Form (DMQ-R SF) was used to assess drinking motives (social, coping, enhancement, and conformity). The reasons for abstaining and limiting drinking (RALD) instrument was used to assess the RALD. Additionally, a set of questions regarding motives to decrease drinking were analysed. The results show that differences were observed between the investigated groups: the current dependent group scored significantly higher on all the dimensions of drinking motives than the current low-risk group and significantly higher on coping, social, and enhancement motives than former heavy drinkers (both groups). The two groups of former heavy drinkers did not differ from each other on drinking motives. The investigated groups differed on the motives to reduce drinking—low-risk users scored the lowest on all the motives, whereas current dependent—the highest. The differences in motives to decrease drinking between current-depended and former heavy drinkers indicate which motives can be associated with the prevention strategies, programmes, and therapeutic approaches.